Hitler, Mussolini : der Staatsbesuch des Führers in Italien - Hansen, Henrich 1895-1976; Dietrich, Otto 1897-1952; Hoffmann, Heinrich 1885-1957 (Raumbild-Verl, 1938)
Stereoscopic photographs of Adolf Hitler's 1938 state visit to Italy